Inisiasi Budaya Pilah Sampah Plastik pada Rumah Tangga di Lingkungan Perumahan - Muhamad Abdul Jumali; Anita Kristina (Research Journal of Social Economics Empowerment, 2026)
The environmental challenge faced by communities living in residential areas is the issue of plastic waste. Many households do not yet understand the classification of waste types and lack the habit of waste segregation. Consequently, this leads to an accumulation of plastic waste. This community service activity, conducted in RT 13, Bumi Candi Asri Housing, Sidoarjo, aims to initiate a culture of plastic waste segregation at the household level to support the creation of a clean and sustainable environment. The methods employed include education on plastic types and direct assistance in plastic sorting. The results indicate a significant increase in community awareness, with 90% of residents now separating plastic waste into saleable categories. This initiative has successfully reduced the volume of plastic waste sent to landfills (TPA) and has also emerged as a new economic source for the residential environment. This activity is expected to strengthen awareness of healthy living behaviors and realize a sustainable environment. .